Prognostic Value of the Malnutrition-inflammation Score in Hospitalization and Mortality on Long-term Hemodialysis - Sá Martins V. (2022)
Objective: Since its development, cumulative evidence has accumulated regarding the prognostic value of the Malnutrition-Inflammation Score (MIS/Kalantar score) prognostic value; however, there is a shortage of recent and large studies with comprehensive statistical methodologies that contribute to support a higher level of evidence and a consensual cutoff. The aim of this study was to assess the strength of MIS association with hospitalization and mortality in a nationwide cohort. Methods: This was a historical cohort study of hemodialysis patients from 25 outpatient centers followed up for 48 months. Univariable and multivariable Cox additive regression models were used to analyze the data. The C-index was estimated to assess the performance of the final model. Results: Two thousand four hundred forty-four patients were analyzed, 59.0% males, 32.0% diabetic, and median age of 71 years (P25 = 60, P75 = 79). During a median period of 45-month follow-up, with a maximum of 48 months (P25 = 31; P75 = 48), 875 patients presented an MIS <5 (35.8%) and 860 patients (35.2%) died. The proportion of deaths was 23.1% for patients with the MIS <5 and 41.9% if the MIS 5 (P <.001). A total of 1,528 patients (62.5%) were hospitalized with a median time to the first hospitalization of 26 months (P25 = 9; P75 = 45). A new cutoff point regarding the risk of death, MIS 6, was identified for this study data set. In multivariable analysis for hospitalization risk, a higher MIS, higher comorbidity index, and arteriovenous graft or catheter increased the risk, whereas higher Kt/V and higher albumin had a protective effect. In multivariable analysis for mortality risk, adjusting for age, albumin, normalized protein catabolic rate, Charlson comorbidity index, interdialytic weight gain, Kt/V, diabetes, hematocrit, and vascular access, patients with the MIS 6 showed a hazard ratio of 1.469 (95% confidence interval: 1.262-1.711; P <.001). Higher age, higher interdialytic weight gain, higher comorbidity index, and catheter increased significantly the risk, whereas higher Kt/V, higher albumin, and higher normalized protein catabolic rate (1.05 g/kg/d) reduced the risk. Conclusion: The MIS maintains its relevant and significant association with hospitalization and mortality.